A review of digital image forensics. (July 2020) - Ferreira, William D.; Ferreira, Cristiane B.R.; da Cruz Júnior, Gelson; Soares, Fabrizzio
Highlights: A comprehensive literature review of digital image forensics. Several techniques for detecting adulterated digital images. A set of references synthesized in textual, tabular, and graphic form. Image tampering detection based on deep learning. Graphical abstract: Abstract: The manipulation of digital images has become very common in recent years. Thus, it is possible to cut, clone, and resize an image very quickly, which makes it challenging to validate the integrity and authenticity of images. Furthermore, digital images can be used by forensic experts in their forensic investigations. In this context, digital image forensics (DIF) has emerged as an essential area of expertise focused on verifying the authenticity and integrity of digital files. This paper presents a literature review of DIF, covering active and passive methods as well as those based on deep learning, and our work presents a vast and updated set of references synthesized in textual, tabular, and graphic form.